A "Worthy” Refugee: Cash as a Diagnostic of "Xeno-Racism" and "Bio-Legitimacy" - Boeyink, Clayton Todd (Refuge, 2019)
The refugee regime structure follows a “xeno-racist” colonial genealogy. In this context, refugee cash transfers represent a biopolitical diagnostic, indicating where refugees are worthy or have the “bio-legitimacy” to reside. This article offers a brief genealogy of different iterations of cash operations, which include cash for repatriation at the end of the Cold War, cash for urban Iraqi refugees in Jordan following the second Gulf War, and the Tanzania government’s recent decision to abruptly shut down a cash project in Nyarugusu refugee camp. Simply stated, where cash is allowed to flow, so too are refugees.